Blast phase of chronic myeloid leukemia with concurrent BCR:ABL1 and SET:NUP214: A report of two cases. Issue 2 (2nd November 2022) - Chen, Yan; Wang, Qian; Cen, Jiannong; Xu, Chao; Tao, Ting‐ting; Xie, Jundan; Shen, Wenhong; Gong, Yanlei; Pan, Jinlan; Yao, Li
Abstract: Chronic myeloid leukemia (CML) is a myeloproliferative neoplasm defined by the presence of t(9;22)(q34;q11.2)/ BCR::ABL1 . Additional chromosomal abnormalities play an important role in the progression to CML. However, the additional fusion gene was rarely reported such as CBFB::MYH11 . In this report, we described two cases of the co‐occurrence of BCR::ABL1 and SET::NUP214 in CML‐BP for the first time, which is associated with poor outcomes during tyrosine kinase inhibitor (TKI) treatment. Meanwhile, we retrospectively analyzed SET::NUP214 fusion transcript of the two cases at initial diagnosis of the CML chronic phase by quantitative RT‐PCR, and detected at a ratio of 1.63% and 1.50%, respectively. SET::NUP214 may promote disease progression during the transformation of CML. This study highlights the importance of extended molecular testing at the initial diagnosis of CML‐CP at TKI resistance and/or disease transformation.